Piezo2 expressed in proprioceptive neurons is essential for skeletal integrity - Assaraf, Eran (Nat Commun, 2020)
In humans, mutations in the PIEZO2 gene, which encodes for a mechanosensitive ion channel, were found to result in skeletal abnormalities including scoliosis and hip dysplasia. Here, we show in mice that loss of Piezo2 expression in the proprioceptive system recapitulates several human skeletal abnormalities. While loss of Piezo2 in chondrogenic or osteogenic lineages does not lead to human-like skeletal abnormalities, its loss in proprioceptive neurons leads to spine malalignment and hip dysplasia. To validate the non-autonomous role of proprioception in hip joint morphogenesis, we studied this process in mice mutant for proprioceptive system regulators Runx3 or Egr3. Loss of Runx3 in the peripheral nervous system, but not in skeletal lineages, leads to similar joint abnormalities, as does Egr3 loss of function. These findings expand the range of known regulatory roles of the proprioception system on the skeleton and provide a central component of the underlying molecular mechanism, namely Piezo2.